Distribution and relative activity of matrix metalloproteinase-2 in human coronal dentin - Boushell, Lee W (Nature Publishing Group, 2011)
The presence of matrix metalloproteinase-2 (MMP-2) in dentin has been reported, but its distribution and activity level in mature human coronal dentin are not well understood. The purpose of this study was to determine the MMP-2 distribution and relative activity in demineralized dentin. Crowns of twenty eight human molars were sectioned into inner (ID), middle (MD), and outer dentin (OD) regions and demineralized. MMP-2 was extracted with 0.33 mol·L(−1) EDTA/2 mol·L(−1) guanidine-HCl, pH 7.4, and MMP-2 concentration was estimated with enzyme-linked immunoabsorbant assay (ELISA). Further characterization was accomplished by Western blotting analysis and gelatin zymography. The mean concentrations of MMP-2 per mg dentin protein in the dentin regions were significantly different (P=0.043): 0.9 ng (ID), 0.4 ng (MD), and 2.2 ng (OD), respectively. The pattern of MMP-2 concentration was OD>ID>MD. Western blotting analysis detected ∼66 and ∼72 kDa immunopositive proteins corresponding to pro- and mature MMP-2, respectively, in the ID and MD, and a ∼66 kDa protein in the OD. Gelatinolytic activity consistent with MMP-2 was detected in all regions. Interestingly, the pattern of levels of Western blot immunodetection and gelatinolytic activity was MD>ID>OD. The concentration of MMP-2 in human coronal dentin was highest in the region of dentin that contains the dentinoenamel junction and least in the middle region of dentin. However, levels of Western blot immunodetection and gelatinolytic activity did not correlate with the estimated regional concentrations of MMP-2, potentially indicating region specific protein interactions.